2020
DOI: 10.3389/fmed.2020.591036
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride-Glucose Index Linked to Hospital Mortality in Critically Ill Stroke: An Observational Multicentre Study on eICU Database

Abstract: The triglyceride-glucose (TyG) index is a reliable surrogate of insulin resistance and a marker for ischemic stroke (IS) incident. Whether the TyG index predicts stroke outcome remains uncertain. This study investigated the prognostic value of the TyG index in critically ill stroke patients. Methods: This was a retrospective observational study that included stroke patients, and all data were extracted from the eICU Collaborative Research Database. The TyG index was calculated as the ln [fasting glucose level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 51 publications
1
47
4
Order By: Relevance
“…It is associated with arterial stiffness 41 , increased risk of cardiovascular disease and worse post-percutaneous coronary intervention outcomes 19 . In stroke, the TyG index has been associated with increased risk of stroke 22 , in-hospital mortality in critically-ill stroke 24 , and early recurrent ischemic lesions 25 . Baseline TyG index has been associated with increased mortality and neurologic deterioration in ischemic stroke 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is associated with arterial stiffness 41 , increased risk of cardiovascular disease and worse post-percutaneous coronary intervention outcomes 19 . In stroke, the TyG index has been associated with increased risk of stroke 22 , in-hospital mortality in critically-ill stroke 24 , and early recurrent ischemic lesions 25 . Baseline TyG index has been associated with increased mortality and neurologic deterioration in ischemic stroke 23 .…”
Section: Discussionmentioning
confidence: 99%
“…While the TyG index has demonstrated predictive effects in major adverse cardiovascular event outcomes in patients with acute coronary disease undergoing percutaneous coronary intervention 19 , and was superior to fasting glucose and hemoglobin A1c (HbA1C) in this setting 20 , it has not been well investigated in stroke populations. While previous authors have found an association between incidence of AIS and TyG index 21,22 , limited studies have reported the effect of the TyG index on post-stroke clinical outcomes or recurrence [23][24][25] , and the relationship of the TyG index in a thrombolyzed patient cohort has been studied scarcely. The only two studies that have investigated the effect of IR on AIS patients' response to thrombolysis both utilized HOMA-IR and were limited by sample size or analyzed only non-diabetic patients 26,27 .…”
mentioning
confidence: 99%
“…Several studies have examined the associations between TyG index and all-cause and cause-specific mortality [ 5 , 6 ]. It has been demonstrated that TyG index was an independent predictor of mortality in patients with type 2 diabetes [ 7 ], hypertension [ 8 ] and stroke [ 9 ]. Besides, the positive relationship was also seen in subclinical myocardial injury [ 10 ], ST-elevation myocardial infarction [ 11 ] and non-ST elevation acute coronary syndrome [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that a higher TyG index is independently associated with the risk of atherosclerotic CVDs, including stroke [13,14]. However, studies which evaluated the possible predictive role of TyG index for the prognosis of patients with acute IS showed inconsistent findings [15][16][17][18][19][20][21][22]. Some studies suggested that a higher TyG index may predict the mortality risk [15,21,22] or poor functional outcome [17][18][19][20][21] in patients with acute IS, but not all studies [16].…”
Section: Introductionmentioning
confidence: 99%